Detection of domoic acid in Mytilus galloprovincialis and Ostrea edulis linked to the presence of Nitzschia bizertensis in Bizerte Lagoon (SW Mediterranean). (5th November 2015) - Bouchouicha-Smida, Donia; Lundholm, Nina; Sahraoui, Inès; Lambert, Christophe; Mabrouk, Hassine Hadj; Hlaili, Asma Sakka
Abstract: Seasonal variation of DA in bivalves was monitored from August 2008 to March 2009 at a shellfish station in Bizerte Lagoon, one of the most important shellfish areas in Tunisia. At the same time, dynamics of potentially toxic diatoms was studied at six stations in the lagoon. Several diatom strains were isolated, maintained in culture and their identification as well as the toxicity was examined. During the study period, domoic acid (DA) was detected in Tunisia, in both mussels ( Mytilus galloprovincialis : 0.13–0.86 μg DA g −1 tissue) and oysters ( Ostrea edulis : 0.42–1.04 μg DA g −1 tissue). The amount of DA in the two species was below the EU guideline limits for shellfish (20 μg DA g −1 ). Within the phytoplankton community, potentially toxic diatoms were observed in high densities (10 4 –10 6 cells l −1 ). Among the 9 established cultured strains, seven were identified as the recently described species Nitzschia bizertensis sp. nov, which is apparently a commonly occurring species in the Bizerte Lagoon. Among tested five strains of N. bizertensis, four were confirmed to be toxin producers, containing 2–7 × 10 −3  pg DA cell −1 during stationary growth phase. Our results indicate for the first time a Nitzschia species, here Nitzschia bizertensis, could be in relation to accumulation of DA in shellfish. Monitoring of DA in phytoplankton and shellfish should be considered for Bizerte Lagoon in order to gain knowledge about the ecology and toxin-production of N. bizertensis and to explore the risk of DA accumulation in the local shellfish industry caused by this species.